2005
DOI: 10.1021/bi047369b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Conformational Changes Coupled to Ligand Photodissociation from the Heme Binding Domain of FixL

Abstract: Using transient absorption spectroscopy and photoacoustic calorimetry (PAC), we have characterized carbon monoxide photodissociation and rebinding to two forms of the heme domain of Bradyrhizobium japonicum FixL. Transient absorption results for the complete heme domain (FixL residues 140-270) and a truncated heme domain (missing 11 residues on the N-teminal end and 14 amino acid residues on the C-terminal end of the full length heme domain) show similar rates for ligand rebinding to the five-coordinate heme d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…In this case, the enthalpic changes for resolvable reactions steps, which occur subsequent to prompt heat release are described as DH i = Àq i . This is how Di Primo et al [40][41][42] reported DH values for CO photodetachment from cytochrome P450 cam and how Larsen and coworkers report their results [44][45][46][47][48][49][50][51][52]. Because we will compare our results to theirs, we follow this precedent in Section 4.…”
Section: Photoacoustic Data Analysismentioning
confidence: 54%
See 3 more Smart Citations
“…In this case, the enthalpic changes for resolvable reactions steps, which occur subsequent to prompt heat release are described as DH i = Àq i . This is how Di Primo et al [40][41][42] reported DH values for CO photodetachment from cytochrome P450 cam and how Larsen and coworkers report their results [44][45][46][47][48][49][50][51][52]. Because we will compare our results to theirs, we follow this precedent in Section 4.…”
Section: Photoacoustic Data Analysismentioning
confidence: 54%
“…We speculate that this conformational change involves the displacement of one or more relatively exposed charges inward, out of contact with solvent, as would occur in the closing of a salt bridge, and that this motion is coupled to changes in ligand mobility with the heme module of the protein. In view of other studies [38,41,52,65], similar conformational changes may be common to heme proteins, and photoacoustic approaches will be useful in their characterization. The photoacoustic signals from cytochrome oxidase systems are particularly complex as they arise from a variety of events following CO photolysis, they seem to be dependent on buffer composition, and protocols to facilitate their resolution and deconvolution will be necessary.…”
Section: Pa Results In High Concentration Sodium Phosphate Buffermentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to optical techniques, such as transient absorption and IR spectroscopy, that monitor the time profile of absorption changes in the chromophore surrounding; photothermal techniques detect the time-dependence of heat/volume changes and therefore are valuable tools for investigating time profiles of optically "silent" processes. So far, photoacoustic calorimetry and transient grating has been successfully applied to study conformational dynamics of photo-induced processes including diatomic ligand migration in globins 3,4 , ligand interactions with oxygen sensor protein FixL 5 , electron and proton transport in heme-copper oxidases 6 and photosystem II as well as photo-isomerization in rhodopsin 7 and conformational dynamics in cryptochrome 8 .…”
Section: Introductionmentioning
confidence: 99%